An overview of the social worker's responsibilities - Vîșcu, Loredana Ileana; Rad, Dana (Technium Social Sciences Journal, 2025)
Social assistance performs a social mediation function, i.e. social assistance is a barometer of power between different social groups. Social assistance is also an instrument through which individuals or micro-groups make their needs known to society by providing transactions between the state and society/individuals/micro-groups. Social work brings to the foreground the relationship between a world of normality and a world of marginality (Bocancea et al, 1999), and this relationship refers to professional values in social work. Professional values are a guide, but not necessarily an outcome of social work activities. This paper aims to give a brief overview of the responsibilities and difficulties of the social worker.